2021
DOI: 10.1111/cen.14541
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term response to cabergoline and multi‐modal treatment in men with macroprolactinoma: Does size really matter?

Abstract: Objective To study the outcome of men with macroprolactinoma following cabergoline treatment based on tumour size. Design Retrospective cohort study. Methods The study included 94 men, divided into three groups according to adenoma diameter: 10–19 mm (Group A, n = 36); 20–39 mm (Group B, n = 41); or ≥40 mm (Group C, giant prolactinomas, n = 17). Patients were followed for a mean of 7.5 years with sellar magnetic resonance imaging, visual fields and hormone measurements. Results Mean baseline prolactin was 767,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This study clearly shows that cabergoline (CAB) is superior to bromocriptine (BRC) in achieving the outcome which is comparable to previously published data. In a recent article by Rudman et al [16], macroprolactinomas in men were controlled with cabergoline in 84% of cases. In another retrospective comparison of CAB and BCR in hyperprolactinemia by Arduc et al [17], CAB was found more effective than BCR in controlling symptoms of hormone excess, normalization of PRL (87.4 vs. 41.4%) and tumor shrinkage (79.8 ± 39.1 vs. 54.1 ± 55.3%).…”
Section: Discussionmentioning
confidence: 98%
“…This study clearly shows that cabergoline (CAB) is superior to bromocriptine (BRC) in achieving the outcome which is comparable to previously published data. In a recent article by Rudman et al [16], macroprolactinomas in men were controlled with cabergoline in 84% of cases. In another retrospective comparison of CAB and BCR in hyperprolactinemia by Arduc et al [17], CAB was found more effective than BCR in controlling symptoms of hormone excess, normalization of PRL (87.4 vs. 41.4%) and tumor shrinkage (79.8 ± 39.1 vs. 54.1 ± 55.3%).…”
Section: Discussionmentioning
confidence: 98%
“…The difference in PRLomas size is already noticeable in children; tumors in boys are typically larger and more invasive than in girls (70 and 38%, respectively) but they are generally more frequent in girls (53)(54)(55)(56)(57). Up to 25% of male PRLomas are represented by giant PRLomas (gPRLomas) (24,31,58,59), defined as PRL-secreting PAs ≥ 4 cm in diameter, often associated with markedly high serum PRL levels and significant extrasellar extension (16,24). The incidence of gPRLomas is estimated at 0.5 to 4.4% of all PAs (60, 61).…”
Section: Epidemiologymentioning
confidence: 99%
“…In men, the diagnosis may be delayed due to unawareness of symptoms, their shaming nature for patients, or the timing of reporting to the physician since their onset (12-14, 19, 25, 26). In addition to the differences mentioned above, PRLomas in men also affect cardiovascular and metabolic risk (12,(27)(28)(29), semen quality and fertility potential (13, [30][31][32][33][34], bone health (12, 35,36), and increase in total body fat (29,37,38), making the role of hyperprolactinemia control essential in men's health.…”
Section: Introductionmentioning
confidence: 99%
“…The RMC pituitary clinic's treatment and follow-up protocol for this cohort of male macroprolactinoma is available in a previously published article [7].…”
Section: Treatment and Follow-up Protocolmentioning
confidence: 99%